Outcome of early control of infection using antibiotics impregnated cement beads in early surgical site infection in operated case of intra articular comminuted fracture (AO C3) of distal femur with ORIF: case report and review of literature - Chaudhari, Kunal; Mahajan, Neetin P.; Sangma, Sunny; Jarika, Ashish Kumar; Talukderg, Pritam (International Journal of Research in Orthopaedics, 2022)
Surgical site infection is the most deleterious complication for any surgery and it’s quite a daunting task for the surgeon to manage such post op events which also takes a great toll on patients’ health physically as well as financially. Here we are presenting one such case report of early SSI effectively managed with antibiotic cement beads incorporation locally. We report a 65 year old male patient case of left sided comminuted distal femur fracture who was managed operatively with open reduction and internal fixation with 8 holes distal femur plate. Patient developed early SSI and was managed with debridement and antibiotic cement beads which was removed 6 weeks later. Here, we bring to the fore relevant findings to conclude the advantages of antibiotic cement beads for infected surgical wounds. In our case, early intervention resulted in full recovery of the patient from surgical site infection, early rehabilitation of joint mobility, decreased hospital stay and expenses. Looking at the advantages it is concluded from our study that locally impregnated antibiotic beads confers higher effectivity, compliance and cost benefits to the patient.